Determinants of Postoperative Hypothermia Among Patients Receiving General Anesthesia in a Regional Hospital in Indonesia - Ressa Affillia Suwandi; Cecep Eli Kosasih; Dedi Supriadi (Universitas Pahlawan Tuanku Tambusai, 2026)
Postoperative hypothermia remains a common and clinically significant complication among patients undergoing surgery with general anesthesia. This study aimed to identify determinants associated with postoperative hypothermia in patients receiving general anesthesia at RSUD Majalengka, Indonesia. A quantitative analytic observational design with a cross-sectional approach was applied to 91 postoperative patients selected using total sampling. Data were collected from medical records and direct observation, including age, body mass index (BMI), duration of surgery, and postoperative body temperature. Statistical analyses were conducted using univariate, bivariate (Chi-square), and multivariate logistic regression tests. Results showed that 48.4% of patients experienced postoperative hypothermia. Significant associations were found between hypothermia and BMI (p=0.034), duration of surgery (p=0.002), and age (p=0.009). Multivariate analysis revealed that duration of surgery was the most dominant predictor (OR=3.922; p=0.005), indicating patients undergoing longer procedures had nearly four times higher risk of hypothermia. These findings highlight the importance of intraoperative temperature management, particularly in patients undergoing prolonged surgical procedures.